2017
DOI: 10.1111/1556-4029.13398
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Body Mass on Outdoor Adult Human Decomposition

Abstract: Forensic taphonomy explores factors impacting human decomposition. This study investigated the effect of body mass on the rate and pattern of adult human decomposition. Nine males and three females aged 49-95 years ranging in mass from 73 to 159 kg who were donated to the Complex for Forensic Anthropology Research between December 2012 and September 2015 were included in this study. Kelvin accumulated degree days (KADD) were used to assess the thermal energy required for subjects to reach several total body sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…Based on these data, we assume that the median mass of the human sample from Connor et al [23] was no less than 80 kg, so the difference in median between pig and human sample was no less than 45 kg experimental findings supporting the claim that in a mass range of 73-159 kg (N = 12, nine cadavers over 100 kg, i.e. obese, adipose bodies) decomposition rate is not significantly related to human body mass [54], all rigorous studies revealed that in a forensically relevant mass range (10-90 kg) small pig cadavers decompose significantly faster than large ones [55][56][57][58][59]. This difference appeared only in the case of insect-colonized carcasses [56] and has been suggested to result from less efficient active decay in larger cadavers, as a consequence of competition over carrion between different insect taxa [45,59].…”
Section: Pigsmentioning
confidence: 54%
“…Based on these data, we assume that the median mass of the human sample from Connor et al [23] was no less than 80 kg, so the difference in median between pig and human sample was no less than 45 kg experimental findings supporting the claim that in a mass range of 73-159 kg (N = 12, nine cadavers over 100 kg, i.e. obese, adipose bodies) decomposition rate is not significantly related to human body mass [54], all rigorous studies revealed that in a forensically relevant mass range (10-90 kg) small pig cadavers decompose significantly faster than large ones [55][56][57][58][59]. This difference appeared only in the case of insect-colonized carcasses [56] and has been suggested to result from less efficient active decay in larger cadavers, as a consequence of competition over carrion between different insect taxa [45,59].…”
Section: Pigsmentioning
confidence: 54%
“…The study conducted provides an in-depth analysis of the variables influencing cadaver decomposition, primarily focusing on insect succession patterns and the effects of seasonal changes (Moura et al 1997;Tabor et al 2004;Corrêa et al 2014). The approach taken to explore these variables was an integrated one, combining both subjective and objective measures, which substantially enhanced the precision and dependability of PMI min estimates (Cross & Simmons 2010;Lynch-Aird et al 2015;Roberts et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…To determine how abundance patterns differed with resource change for common carrion insects, we used total body score (TBS) as a proxy for resource change, using the method by Megyesi et al (2005). TBS is a commonly used and objective measure of decomposition state and indicator of resource change (Nawrocka et al 2016;Connor et al 2017;Roberts et al 2017;Dawson et al 2021b). We applied a separate numeric value based on the physical decomposition of the remains to each body region (head, torso and limbs) and combined these values together to provide an overall score of the decomposition rate.…”
Section: Discussionmentioning
confidence: 99%